Święty Józef w przestrzeni kulturowej tradycyjnej wsi .......... 597 - Kurek, Halina; Serafin-Wicher, Aleksandra (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
SAINT JOSEPH IN THE CULTURAL SPACE OF A TRADITIONAL VILLAGEThe traditional Polish village is a cultural space in which Roman Catholicism, including the cult of Saint Joseph, has become an integral part of daily life. Although the Gospels provide limited information on Saint Joseph, his figure has significantly impacted the sacralisation of various aspects of rural life, including the household (family), space, time, and work. The sacralisation of rural cultural areas manifested in practices such as naming villages after the Saint, as well as the construction of shrines featuring depictions of Joseph equipped with with carpentry tools. Even the home garden could be sanctified by growing Saint Joseph’s lilies in it. The cult of Saint Joseph has also had a significant impact on the agricultural calendar, determining some farming practices and associated beliefs. In folk tradition, Saint Joseph was also linked to customs and rites of everyday rurallife, such as sowing peas, planting cabbages, or repairing stork nests.